- Analisis Yuridis Kepailitan Badan Usaha Milik Negara Berbentuk Persero: -Studi Putusan PT. Merpati Nusantara Airlines - CLARISSA AYANG JELITA; Abdullah Fikri (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This Study Analyzes The Bankruptcy Status Of BUMN In The Form Of A Limited Liability Company, With A Case Study Of PT Merpati Nusantara Airlines Based On Decision Number 04/Pdt.Sus-PAILIT/2016/PN.Niaga.Jkt.Pst And Decision Number 5/Pdt.Sus-Pembanalan Perdamaian/2022/PN.Niaga Sby. The Results Of The Study Indicate Inconsistencies In The Application Of Article 2 Paragraph (5) Of The Bankruptcy Law And PKPU Regarding Legal Standing In Bankruptcy Applications Against BUMN. In Addition, This Study Discusses The Responsibility Of Directors Based On The Business Judgment Rule, Which Determines That Directors Cannot Be Held Personally Liable If They Have Acted In Good Faith.